Alkylation treatment of the Mexican Axolotl: An approach to the induction of new mutations. - Ortiz, Maria Fernanda. (University of Ottawa (Canada), 1977)
In order to obtain new mutants in the axolotl, Ambystoma mexicanum, that could be used for future genetic studies, EMS treatments have been given to adult females. Our results indicate a reduced fertility among the eggs from treated females, as well as increased lethality during embryonic development. Abnormal larvae have been obtained from these embryos. Whether we have succeeded in inducing new mutations, or whether the abnormalities are only due to the teratogenic effects of the EMS, still has to be tested when the animals mature. No external signs of haploidy have been observed among these larvae, except in one case. Tail-tip squashes of this larva revealed the normal number of nucleoli. Superovulation has not been observed among the treated females. Instead, our results suggest that EMS is suppressing ovulation. To pinpoint the effects of EMS on germ cells, treatment of various concentrations have been given to mature, spawned sperm. The sperm were used to artificially inseminate newly laid eggs. Our results show that increasing concentrations of EMS reduce the fertility of eggs inseminated with treated sperm. DNA isolated from 3H-EMS treated sperm has shown approximately 1 ethylation per 1,000 nucleotides. In spite of this, abnormalities have not been observed among embryos from EMS treated sperm, and therefore, no increased lethality has been obtained. The possibility that dominant lethal induction by EMS, in the axolotl, is due to damage of extranuclear components is discussed. Possible experiments that would bring some light to this subject are proposed.
Keywords: Biology, Molecular.